1998
DOI: 10.1083/jcb.143.5.1341
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Endothelial Cells in Multicellular Spheroids Prevents Apoptosis and Induces Differentiation

Abstract: Single endothelial cells (EC) seeded in suspension culture rapidly undergo apoptosis. Addition of survival factors, such as VEGF and FGF-2, does not prevent apoptosis of suspended EC. However, when cells are allowed to establish cell–cell contacts, they become responsive to the activities of survival factors. These observations have led to the development of a three-dimensional spheroid model of EC differentiation. EC spheroids remodel over time to establish a differentiated surface layer of EC and a center of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
451
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(468 citation statements)
references
References 51 publications
13
451
1
3
Order By: Relevance
“…HUVEC multicellular spheroids form and survive in the absence of integrin ligation Korff and Augustin (1998) reported that integration of HUVEC in multicellular spheroids prevented anoikis, thereby allowing the study of non-matrix adherent HUVEC over prolonged periods of time. Anti-VEcadherin monoclonal antibody (mAb) or Ca 2 þ depletion prevented spheroid formation for at least 24 h, whereas blocking mAbs against a2, a3, a5, a6, b1, aVb3, aVb5 integrins or PECAM-1, or a peptidic aVb3/aVb5 inhibitor (EMD121974), alone or in combination, did not (Supplementary Figure S2a, and not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HUVEC multicellular spheroids form and survive in the absence of integrin ligation Korff and Augustin (1998) reported that integration of HUVEC in multicellular spheroids prevented anoikis, thereby allowing the study of non-matrix adherent HUVEC over prolonged periods of time. Anti-VEcadherin monoclonal antibody (mAb) or Ca 2 þ depletion prevented spheroid formation for at least 24 h, whereas blocking mAbs against a2, a3, a5, a6, b1, aVb3, aVb5 integrins or PECAM-1, or a peptidic aVb3/aVb5 inhibitor (EMD121974), alone or in combination, did not (Supplementary Figure S2a, and not shown).…”
Section: Resultsmentioning
confidence: 99%
“…This work was initiated to investigate whether integrindependent adhesion may modulate endothelial cell response to TNF and to identify the associated intracellular signaling events. As a main model, we used the endothelial cell spheroid model reported by Korff and Augustin (1998). It allows bypassing anoikis that rapidly occurs in single-cell suspensions (Meredith et al, 1993), thereby allowing to keep HUVEC viable for the duration of the experiment under conditions of integrin-independent but VE-cadherin-dependent adhesion (Spagnuolo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…22 A total of 10 4 H358a cells in 0.1 ml of complete medium were plated in 96-well plates, whereas Gene Therapy 10 5 cells in 1 ml were used in 24-well plates. To prevent cell attachment, plates were coated with 1% medium agar.…”
Section: Cell Death Analysismentioning
confidence: 99%
“…The preparation of cell spheroids was performed as described previously (Korff & Augustin, 1998). Briefly, subconfluent monolayers of HUVECs were trypsinized and suspended in endothelial cell basal medium (ECBM, Promocell, Heidelberg, Germany)…”
Section: Spheroid Sprouting Assaymentioning
confidence: 99%